2009
DOI: 10.1103/physrevb.79.054526
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic itinerant magnetism and spin fluctuations inBaFe2As2: A neutron scattering study

Abstract: Neutron scattering measurements were performed to investigate magnetic excitations in a single-crystal sample of the ternary iron arsenide BaFe 2 As 2 , a parent compound of a recently discovered family of Fe-based superconductors. In the ordered state, we observe low energy spin-wave excitations with a gap energy ⌬ = 9.8͑4͒ meV. The in-plane spin-wave velocity v ab and out-of-plane spin-wave velocity v c measured at 12 meV are 280͑150͒ and 57͑7͒ meV Å, respectively. At high energy, we observe anisotropic scat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
209
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(236 citation statements)
references
References 26 publications
25
209
2
Order By: Relevance
“…For the undoped materials the spin wave dispersion relations have been measured for the SrFe 2 As 2 [40], CaFe 2 As 2 [41,42], and BaFe 2 As 2 [43,44] systems, and the overall spin dynamics for the three systems are quite similar as shown in Table 3. These studies reveal that the spin dynamics are quite energetic, with a spin wave bandwidth ~0.2 eV as shown in Fig.…”
Section: Iron Spin Wavesmentioning
confidence: 80%
“…For the undoped materials the spin wave dispersion relations have been measured for the SrFe 2 As 2 [40], CaFe 2 As 2 [41,42], and BaFe 2 As 2 [43,44] systems, and the overall spin dynamics for the three systems are quite similar as shown in Table 3. These studies reveal that the spin dynamics are quite energetic, with a spin wave bandwidth ~0.2 eV as shown in Fig.…”
Section: Iron Spin Wavesmentioning
confidence: 80%
“…For a spin Hamiltonian, one can starts with a Heisenberg model where the energy of spin waves depends only on the relative orientation of neighboring spins. In the initial neutron scattering experiments on low-energy spin waves in SrFe 2 As 2 (Zhao et al, 2008a) (Matan et al, 2009), a spin gap due to magnetic iron anisotropy was identified. In addition, the low-energy spin waves were described by either a local moment Heisenberg Hamiltonian Zhao et al, 2008a) or the spin excitation continuum from itinerant electrons (Diallo et al, 2009;Matan et al, 2009).…”
Section: A Spin Waves In the Parent Compounds Of Iron-based Superconmentioning
confidence: 99%
“…30,[35][36][37] Instead, the methodology described in Reference 20 was employed. Critical temperatures were determined by comparing linear fits of the order parameter immediately before and after the transition.…”
Section: W E I G H T E D P H a S E F R A C T I O Nmentioning
confidence: 99%